2019
DOI: 10.1519/jpt.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and Predictors of Functional Capacity Decline in Older Adults From a Brazilian Northeastern Hospital

Abstract: Background and Purpose: Older adults face increased risk of loss of functional capacity both before and during hospitalization, so identifying older adults at risk for loss in functional capacity during hospitalization would help researchers and clinicians make informed decisions. This study aims to evaluate functional changes from preadmission (baseline) until discharge of hospitalized older adults and identify predictors of loss in functional capacity. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Our findings align with the literature regarding functional decline in hospitalized older adults. In hospital, mobility has been highlighted as protective against functional decline [ 3 , 23 , 24 ], which aligns with our findings that HEART participants largely maintained functional capacity. However, we found that using a walker was associated with greater functional improvement in the HEART program, which is contrary to one study, which discovered that those who used a walking device prior to hospitalization had a 2.81-times greater likelihood of functional decline compared to those without a device [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings align with the literature regarding functional decline in hospitalized older adults. In hospital, mobility has been highlighted as protective against functional decline [ 3 , 23 , 24 ], which aligns with our findings that HEART participants largely maintained functional capacity. However, we found that using a walker was associated with greater functional improvement in the HEART program, which is contrary to one study, which discovered that those who used a walking device prior to hospitalization had a 2.81-times greater likelihood of functional decline compared to those without a device [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it is possible that race may moderate the main effect of delirium and function in samples that have higher levels of both delirium and lower function in hospitalized persons living with dementia. In addition, this study did not assess and consequently did not control for other potential factors, such as medications, 2,22 depression, 20,22 and social support, 21 that may influence the moderating role of race on the relationship between delirium and physical function among hospitalized older adults. Subsequent investigations should explore the extent to which these factors can influence the moderating role of age, sex, and race on the association between delirium severity and physical function.…”
Section: Discussionmentioning
confidence: 99%
“…These factors have been previously associated with delirium severity or physical function. 2,16,18,20,21,33,34 Education, marital status, and comorbidities were gathered through chart review, with comorbidities assessed using the Charlson Comorbidity Index. 35 Cognition was evaluated using SLUMS, which measures various aspects of memory, including orientation, problem-solving, and recall.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive impairment has been proven to be a risk factor for PF decline among older adults ( Arias-Merino et al, 2012 ; Ha and Kim, 2014 ). Several studies on the trajectories of functional capacity decline have revealed that participants with worse CF at baseline exhibited larger PF decline ( Dodge et al, 2005 ; Helvik et al, 2015 ), and older adults with lower levels of cognition are more likely to decline in functional capacity ( Menezes et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%